Umbilical Coiling Index as a Marker of Perinatal Outcome: An Analytical Study - T. Chitra; Y. S. Sushanth; S. Raghavan (Hindawi Limited, 2012)
Objectives. To measure umbilical coiling index (UCI) postnatally and to study the association of normocoiling, hypocoiling and hypercoiling to maternal and perinatal outcome. Method(s). One thousand antenatal women who went into labour were studied and umbilical coiling index calculated at the time of delivery. UCI was determined by dividing the total number of coils by the total umbilical cord length in centimeters. Its association with various maternal and perinatal risk factors were noted. The statistical tests were the Chi-square test and assessed with SPSS version 13.0 software and statistically analyzed. P value of less than 0.05 was regarded as statistically significant. Results. The mean umbilical coiling index was found to be 0.24 ± 0.09. Hypocoiling (<0.12) was found to be significantly associated with hypertensive disorders, abruptio placentae, preterm labour, oligohydramnios, and fetal heart rate abnormalities. Hypercoiling (>0.36) was found to be associated with diabetes mellitus, polyhydramnios, cesarean delivery, congenital anomalies, and respiratory distress of the newborn. Conclusion. Abnormal umbilical coiling index is associated with several antenatal and perinatal adverse features.